Efficacy Of Cyproterone Acetate And Drosperinone Containing Cocps In Treatment Of Hirsutism In Patients With PCOS - Sarfraz, Nazish; Akram, Humera; Abbas, Afroza; Shaheen, Sadaf; Zafar, Rida; Eesha Yaqoob (Journal of Rawalpindi Medical College, 2023)
Introduction: Hirsutism is a condition characterized by excess hair growth on the face, chest, and/or back in women and it is often caused by an imbalance of hormones, such as androgens. OCPs prove to be effective in reducing hirsutism in patients with PCOS by inhibiting the production of androgens and decreasing the activity of androgen receptors. OCPs may have additional benefits for patients with PCOS, such as regulating menstrual cycles, improving fertility, and reducing the risk of endometrial cancer. However, OCPs may not be suitable for all women with PCOS. Methods: The study was conducted to investigate the effectiveness of these OCPs in reducing hirsutism in PCOS patients. In the study, 80 participants were included, 40 in the intervention group and 40 in the control group. The intervention group received a combination oral contraceptive pill containing cyproterone acetate and drosperinone (COCP) for a period of 6 months, while the control group received a placebo. Hirsutism was assessed at baseline and at the end of the 6-month treatment period using the Ferriman-Gallwey score. The primary outcome measure was the change in Ferriman-Gallwey score from baseline to the end of the treatment period. Results: The study found that OCPs containing cyproterone acetate and drosperinone were more effective in reducing hirsutism in patients with PCOS compared to OCPs containing levonorgestrel. Conclusion: It is important to note that OCPs may not be appropriate for all women with PCOS, therefore it’s crucial to explore the risks and advantages with a healthcare professional before beginning therapy.